PENGARUH REKRUTMEN POLITIK PARTAI KEADILAN DAN PERSATUAN INDONESIA (PKP INDONESIA) TERHADAP PEROLEHAN SUARA PADA PEMILIHAN UMUM TAHUN 2019 DI KABUPATEN KAMPAR - Ririn Ayu Lestari; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
cal parties are formed to carry out their duties, mains and functions as a sub-system of democracy. There are 4 functions of political parties, namely political communication, political socialization, political recruitment and conflict management. The 2019 simultaneous general elections which were held on April 17, 2019 combined the legislative and presidential elections simultaneously. Legislative elections are elections for DPR RI, DPD, DPRD which are held simultaneously. In the context of legislative elections, parties must carry out one of the functions of political parties, namely as a means of public participation in political activities through the political recruitment process. This is also done by PKP Indonesia as a party that has long and experience in general elections but this year has interesting problems to research, namely 1). There was a shrinkage of the electoral areas that followed. 2). The occurrence of significant votes in electoral areas IV. 3). There was an increase in the vote acquisition by 47.9% in the first electoral district of Kampar Regency.This study aims to examine the factors that are considered in Political Recruitment and the role of the Political Recruitment of the Indonesian Justice and Unity Party (PKP Indonesia) in the determination of legislative candidates for party performance (vote acquisition) in the 2019 General Election in Kampar Regency. This research is a descriptive study with a qualitative approach. The location of this research was conducted in Kampar Regency. Data collection techniques used are through interviews and documentation. The data analysis technique used is an interactive analysis model.The results of the study concluded that based on the researchers' observations and analysis, 1). PKP Indonesia implements an open recruitment mechanism where the requirements and procedures for presenting a character can be widely known so that all levels of society can register. 2). The modality that is highly considered by PKP Indonesia is social capital. This can be seen from recruiting legislative candidates based on the size of their influence in the community. 3). The implementation of the document that encourages PKP Indonesia to use the ball-pick method of legislative candidates shows that the cadre recruitment of legislative candidates in the Indonesian PKP Kampar Regency is weak. 4). The recruitment strategy and pattern carried out by PKP Indonesia was quite successful even though it only passed 1 person to become a front member. Because the PKP Indonesia's target is to pass Kardinal Kasim as chairman to return to the seat of the Kampar Regency DPRD.Keywords: Recruitment, regeneration, 2019 elections, modalities, recruitment success factors